2016
DOI: 10.1093/ije/dyw089
|View full text |Cite
|
Sign up to set email alerts
|

Social relationships and cognitive decline: a systematic review and meta-analysis of longitudinal cohort studies

Abstract: Despite heterogeneity in study design and measures, our meta-analyses show that multiple aspects of social relationships are associated with cognitive decline. As evidence for publication bias was found, the association might be overestimated and should therefore be interpreted with caution. Future studies are needed to better define the mechanisms underlying these associations. Potential causality of this prognostic association should be examined in future randomized controlled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
232
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(262 citation statements)
references
References 106 publications
23
232
3
4
Order By: Relevance
“…These results are consistent with some but not other previous research . For instance, Griffin et al found that loneliness correlated with lower cognitive function whereas social isolation was longitudinally associated with worse cognitive performance in older Americans (n = 6654).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with some but not other previous research . For instance, Griffin et al found that loneliness correlated with lower cognitive function whereas social isolation was longitudinally associated with worse cognitive performance in older Americans (n = 6654).…”
Section: Discussionsupporting
confidence: 91%
“…Over the past decade, the study of loneliness and social isolation as potential risk factors for cognitive decline has gained increasing attention. Previous studies have suggested that being alone or never married, low frequency of interactions, small social network size, or negative experiences of social support predict steeper cognitive decline . Moreover, a recent meta‐analysis of longitudinal population‐based studies found evidence that loneliness is also associated with an increased risk of dementia …”
Section: Introductionmentioning
confidence: 99%
“…Thus, identification and management of frailty and cognitive impairment are essential for enhancing health in later years. In addition, in accordance with previous studies, the present findings show a beneficial effect of social contact in terms of people's cognition . Participants who were in more frequent contact with their child showed a smaller percentage of cognitive decline compared with those with infrequent contact.…”
Section: Discussionsupporting
confidence: 93%
“…Tracking cross-level interactions among networks may also offer new approaches for therapeutic intervention and manipulation. For example, a recent meta-analysis suggested a possible association between aspects of social relationships and cognitive decline 132 . Mechanisms of brain networks and social networks become intertwined (Fig.…”
Section: Current Frontiersmentioning
confidence: 99%